The relationship between protective factors and a measure of psychological resistance in women diagnosed with breast cancer - Delila Lisica; Jadranka Kolenović-Ðapo; Amela Džubur; Damir Abdulahović; Malik Ejubović (Medicinski glasnik, 2019)
Aim: To examine the relationship of protective factors (self-esteem, optimism, proactive coping), and a measure of psychological resistance in women diagnosed with breast cancer, and the contribution of protective factors in explaining the criterion of posttraumatic growth. Methods: The study included 100 women diagnosed with breast cancer. To examine optimism the Scale of Dispositional Optimism and Pessimism, the Scale of Self-esteem for self-esteem and the Scale of Proactive Coping for proactive coping were used. The posttraumatic growth measured five factors: relating to others, new possibilities, personal strength, spiritual changes, appreciation of life. Results: Self-esteem, optimism and proactive coping were associated with posttraumatic growth and its factors: new possibilities, personal strength, appreciation of life. Optimism and proactive coping positively corelated also with relating to others. Final model of posttraumatic growth in all three steps (self-esteem, optimism, proactive coping) explained 20.4% variability of the posttraumatic growth total score. Conclusion: Posttraumatic growth does not mean a decrease in trauma, but leads to a change in the perception and view of life. It refers to more favourable management and use of its own resources, relying on its own strengths and capabilities, identifying new opportunities and connecting with others.
Keywords: optimism; posttraumatic growth; proactive coping; self-esteem